If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y + 16 = 4y + -16 Reorder the terms: 16 + 8y = 4y + -16 Reorder the terms: 16 + 8y = -16 + 4y Solving 16 + 8y = -16 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. 16 + 8y + -4y = -16 + 4y + -4y Combine like terms: 8y + -4y = 4y 16 + 4y = -16 + 4y + -4y Combine like terms: 4y + -4y = 0 16 + 4y = -16 + 0 16 + 4y = -16 Add '-16' to each side of the equation. 16 + -16 + 4y = -16 + -16 Combine like terms: 16 + -16 = 0 0 + 4y = -16 + -16 4y = -16 + -16 Combine like terms: -16 + -16 = -32 4y = -32 Divide each side by '4'. y = -8 Simplifying y = -8
| 9x^2+2=308 | | 9+x-5=-10 | | 6y+8=-4y-4 | | cos(4x)cos(x)+sin(4x)sin(x)=0 | | 7y-2=3y-10 | | 10=-15+5x | | X^2+2x+33=-3 | | 2x-x+3=9 | | in(x+5)=2 | | 1/2x+5=120 | | 7n-15=69 | | -(2+7x)= | | (x+15)(x+15)+5=50 | | 3(x-6)+4=30x | | 3(x-6)+4=20x | | 3x+x+0.67x=28 | | -15=-10-5x | | 3(x-6)+4=15x | | 5n-20=40 | | g=6f+h | | 26=4(u+6)-6u | | F(n)=2n-11 | | 50=4w+10 | | X+10=2x-50 | | -2x+(-28)=20 | | V=5k+t | | 4x-15=70 | | 12x^2+3x=17+x | | 8(k-5)+7k=-115 | | t(3t+19)=40 | | 5-7x=34 | | (x+6)(x-2)(x+3)=264 |